Análise espaço-temporal do ictioplâncton em uma sub-bacia do alto rio Paraguai: conhecendo sua contribuição para o Pantanal brasileiro. - Souza, Mateus Babichi Veiga de (2023)
The spatial and temporal distribution of ichthyoplankton, taxonomic composition, and its relation to environmental factors were analyzed in the upper Taquari River sub-basin, upper Paraguay River, aiming at the conservation of Pantanal ichthyofauna. Egg and larval collections were conducted at eleven sampling points between October and March of 2017/2018 and 2018/2019. Significant differences were observed between collection points, months, and years, with higher ichthyoplankton densities in the Coxim and Taquari rivers, particularly between November and January. Twenty-eight genera and/or species of fish were identified, including ten long-distance migratory species. Eggs density showed a negative correlation with water temperature and rainfall. For larvae, water transparency and rainfall were both significant, negatively influencing larval abundance. However, different species tend to occur in environments with distinct abiotic qualities. Yolk-sac, pre-flexion, and flexion larval development stages were distributed throughout the sub-basin, especially near the Pantanal. Considering the data and analyses presented in this study, the importance of connectivity between these environments, specifically between the plateau and Pantanal, is evident, highlighting the significance of the entire sub-basin for fish reproductive processes. Thus, studies highlighting ecological processes affecting ichthyoplankton distribution provide valuable information for ecosystem conservation and contribute to fisheries stock management.